Analysis of electrically evoked compound action potential of the auditory nerve in children with bilateral cochlear implants - Caldas,Fernanda Ferreira (2016)
ABSTRACT INTRODUCTION: The cochlear implant device has the capacity to measure the electrically evoked compound action potential of the auditory nerve. The neural response telemetry is used in order to measure the electrically evoked compound action potential of the auditory nerve. OBJECTIVE: To analyze the electrically evoked compound action potential, through the neural response telemetry, in children with bilateral cochlear implants. METHODS: This is an analytical, prospective, longitudinal, historical cohort study. Six children, aged 1-4 years, with bilateral cochlear implant were assessed at five different intervals during their first year of cochlear implant use. RESULTS: There were significant differences in follow-up time (p = 0.0082) and electrode position (p = 0.0019) in the T-NRT measure. There was a significant difference in the interaction between time of follow-up and electrode position (p = 0.0143) when measuring the N1-P1 wave amplitude between the three electrodes at each time of follow-up. CONCLUSION: The electrically evoked compound action potential measurement using neural response telemetry in children with bilateral cochlear implants during the first year of follow-up was effective in demonstrating the synchronized bilateral development of the peripheral auditory pathways in the studied population.